Tangent Line, Velocity, Derivative and Differentiability instant rate of change and approximation of the function Motivation: what do tangent line and velocity have in common? Euclid: The tangent is a line that touches a curve at just one point. Works for circles: Euclid: The tangent is a line that touches a curve at just one point. Works for circles: x Does NOT work for sin(x)! x Modern: The tangent is the limiting position of the secant line (if exists). Tangent = lim Secant f(t) t→x Slope of Slope of = lim Tangent t→x Secant f(t)-f(x) slope of ______ = t-x secant f(t)-f(x) t-x f(x) x f (t) − f (x) Slope of = lim Tangent t→x t−x t EXAMPLES f (t) − f (x) Slope of = lim Tangent t→x t−x EXAMPLE 1. Find slope of the tangent line to the graph of f (x) = x2 − 4 at point (3, 5). f (t) − f (x) Slope of = lim Tangent t→x t−x EXAMPLE 1. Find slope of the tangent line to the graph of f (x) = x2 − 4 at point (3, 5). 2 2 (t − 4) − (x − 4) Slope of = lim Tangent t→x t−x f (t) − f (x) Slope of = lim Tangent t→x t−x EXAMPLE 1. Find slope of the tangent line to the graph of f (x) = x2 − 4 at point (3, 5). 2 2 (t − 4) − (x − 4) Slope of = lim Tangent t→x t−x t2 − x2 (t − x)(t + x) = lim = lim = 2x t→x t − x t→x t−x f (t) − f (x) Slope of = lim Tangent t→x t−x EXAMPLE 1. Find slope of the tangent line to the graph of f (x) = x2 − 4 at point (3, 5). 2 2 (t − 4) − (x − 4) Slope of = lim Tangent t→x t−x t2 − x2 (t − x)(t + x) = lim = lim = 2x t→x t − x t→x t−x At x = 3, (y = 5 is irrelevant) Slope of Tangent = 6 Velocity: How fast the position s(x) is changing. x=3 h x=0 4 0 h4 h h x=4 4 h 4 h x=2 x=1 h 4 1 s h x=5 Average = Velocity s(x + h) − s(x) = h s(x + h) − s(x) Instantaneous = lim Velocity h→0 h EXAMPLES s(x + h) − s(x) Instant. = lim Velocity h→0 h EXAMPLE 2. Motion of the particle along a line is described by s(x) = 1 + cos(x). Find instantaneous velocity at moment x = 2. s(x + h) − s(x) Instant. = lim Velocity h→0 h EXAMPLE 2. Motion of the particle along a line is described by s(x) = 1 + cos(x). Find instantaneous velocity at moment x = 2. (1 + cos(x + h)) − (1 + cos(x)) Instant. = lim Velocity h→0 h s(x + h) − s(x) Instant. = lim Velocity h→0 h EXAMPLE 2. Motion of the particle along a line is described by s(x) = 1 + cos(x). Find instantaneous velocity at moment x = 2. (1 + cos(x + h)) − (1 + cos(x)) Instant. = lim Velocity h→0 h cos(x + h) − cos(x) = lim h→0 h cos(x + h) − cos(x) = lim h→0 h (using cos(x + h) = cos(x) cos(h) − sin(x) sin(h)) cos(x + h) − cos(x) = lim h→0 h (using cos(x + h) = cos(x) cos(h) − sin(x) sin(h)) cos(x) cos(h) − sin(x) sin(h) − cos(x) = lim h→0 h cos(x + h) − cos(x) = lim h→0 h (using cos(x + h) = cos(x) cos(h) − sin(x) sin(h)) cos(x) cos(h) − sin(x) sin(h) − cos(x) = lim h→0 h cos(h) − 1 sin(h) = cos(x) lim − sin(x) lim x→0 x→0 h h = − sin(x) cos(x + h) − cos(x) = lim h→0 h (using cos(x + h) = cos(x) cos(h) − sin(x) sin(h)) cos(x) cos(h) − sin(x) sin(h) − cos(x) = lim h→0 h cos(h) − 1 sin(h) = cos(x) lim − sin(x) lim x→0 x→0 h h = − sin(x) At x = 2, Instantaneous Velocity = − sin(2) Compare f (t) − f (x) Slope of = lim Tangent t→x t−x s(x + h) − s(x) Instant. = lim Velocity τ →0 h Compare f (t) − f (x) Slope of = lim Tangent t→x t−x s(x + h) − s(x) Instant. = lim Velocity τ →0 h Equivalent up to the substitution f = s, t−x=h Compare f (t) − f (x) Slope of = lim Tangent t→x t−x s(x + h) − s(x) Instant. = lim Velocity τ →0 h Equivalent up to the substitution f = s, Is it the same thing? t−x=h Definition of the Derivative putting things together Slope of Tangent Instant. Velocity s(x + h) − s(x) f (t) − f (x) lim lim t→x h→0 h t−x Rate of Change s(t + ∆t) − s(t) lim ∆t→0 ∆t Slope of Tangent Rate of Change Instant. Velocity s(x + h) − s(x) f (t) − f (x) lim lim t→x h→0 h t−x s(t + ∆t) − s(t) lim ∆t→0 ∆t Definition: Derivative of f (x) at point x is f (t) − f (x) f (x) = lim t→x t−x 0 f (x + h) − f (x) or, f (x) = lim h→0 h 0 Illustration Slope of Tangent y slope=f '(x) Instant. Velocity Rate of Change y=f(x) x=3 h x x=0 4 0 x=4 h4 4 x=2 4 4 h c s'(x) 1 s x=1 Velocity = s'(x) h Rate of = Q'(t) Change x=5 Q(t) EXAMPLES f (t) − f (x) f (x) = lim t→x t−x 0 EXAMPLE 3. Evaluate f 0(x) using definition of derivative, if f (x) = x3 + 2x. f (t) − f (x) f (x) = lim t→x t−x 0 EXAMPLE 3. Evaluate f 0(x) using definition of derivative, if f (x) = x3 + 2x. 3 3 (t + 2t) − (x − 2x) 0 f (x) = lim t→x t−x f (t) − f (x) f (x) = lim t→x t−x 0 EXAMPLE 3. Evaluate f 0(x) using definition of derivative, if f (x) = x3 + 2x. 3 3 (t + 2t) − (x − 2x) 0 f (x) = lim t→x t−x (t3 − x3) + (2t − 2x) = lim t→x t−x f (t) − f (x) f (x) = lim t→x t−x 0 EXAMPLE 3. Evaluate f 0(x) using definition of derivative, if f (x) = x3 + 2x. 3 3 (t + 2t) − (x − 2x) 0 f (x) = lim t→x t−x (t3 − x3) + (2t − 2x) = lim t→x t−x t3 − x3 2t − 2x = lim + lim t→x t − x t→x t − x Consider t3 − x3 2t − 2x = lim + lim t→x t − x t→x t − x Consider t3 − x3 2t − 2x = lim + lim t→x t − x t→x t − x (t − x)(t2 + tx + x2) 2(t − x) = lim + lim t→x t→x (t − x) (t − x) = 1 · (x2 + x2 + x2) + 2 = 3x2 + 2 f (x + h) − f (x) f (x) = lim h→0 h 0 0 EXAMPLE 4. Evaluate f (x) using definition of √ derivative, if f (x) = x. f (x + h) − f (x) f (x) = lim h→0 h 0 0 EXAMPLE 4. Evaluate f (x) using definition of √ derivative, if f (x) = x. √ √ x+h− x 0 f (x) = lim h→0 h f (x + h) − f (x) f (x) = lim h→0 h 0 0 EXAMPLE 4. Evaluate f (x) using definition of √ derivative, if f (x) = x. √ √ x+h− x 0 f (x) = lim h→0 h √ √ √ √ ( x + h − x) ( x + h + x) √ = lim √ h→0 h ( x + h + x) f (x + h) − f (x) f (x) = lim h→0 h 0 0 EXAMPLE 4. Evaluate f (x) using definition of √ derivative, if f (x) = x. √ √ x+h− x 0 f (x) = lim h→0 h √ √ √ √ ( x + h − x) ( x + h + x) √ = lim √ h→0 h ( x + h + x) 1 1 (x + h) − x √ = √ = lim √ √ =√ h→0 h( x + h + x+ x 2 x x) The Differential problem of linear approximation Approximating function with a line f (x+h) = f (x)+m·h+o(h) where o(h) lim =0 h→0 h Motion along a line: y = y0 + m · h slope = m A f(x) y mh h x0 o(h) mh h x y0 A f(x+h) slope=m x+h Approximating function with a line f (x+h) = f (x)+m·h+o(h) where o(h) lim =0 h→0 h Motion along a line: y = y0 + m · h What is m ? slope = m A f(x) y mh h x0 o(h) mh h x y0 A f(x+h) slope=m x+h Definition. Function f (x) is differentiable at x if there exists a number m such that f (x + h) = f (x) + m · h + o(h) o(h) where lim =0 h→0 h (o(h) “o”-little is a quantity of the order of magnitude smaller then h). Differential: df (x)hhi = m · h Compute m. Assume function f (x) is differenti able: f (x + h) = f (x) + m · h + o(h). Solving for m and rearranging, f (x + h) − f (x) o(h) =m+ h h Compute m. Assume function f (x) is differenti able: f (x + h) = f (x) + m · h + o(h). Solving for m and rearranging, f (x + h) − f (x) o(h) =m+ h h differentiability requires o(h) limh→0 h = 0 therefore, f (x + h) − f (x) lim =m h→0 h Compute m. Assume function f (x) is differenti able: f (x + h) = f (x) + m · h + o(h). Solving for m and rearranging, f (x + h) − f (x) o(h) =m+ h h differentiability requires o(h) limh→0 h = 0 therefore, f (x + h) − f (x) lim =m h→0 h or f 0(x) exists and f 0(x) = m. Differentiability implies Derivative! f (x + h) = f (x) + m · h + o(h) EXAMPLE 5. Differentiate f (x) = sin(x). f (x + h) = f (x) + m · h + o(h) EXAMPLE 5. Differentiate f (x) = sin(x). sin(x + h) = sin(x) + cos(x)h +[− cos(x)h + sin(x + h) − sin(x)] f (x + h) = f (x) + m · h + o(h) EXAMPLE 5. Differentiate f (x) = sin(x). sin(x + h) = sin(x) + cos(x)h +[− cos(x)h + sin(x + h) − sin(x)] Now, m = f 0(x) = cos(x) and o(h) = [. . .]. f (x + h) = f (x) + m · h + o(h) EXAMPLE 5. Differentiate f (x) = sin(x). sin(x + h) = sin(x) + cos(x)h +[− cos(x)h + sin(x + h) − sin(x)] Now, m = f 0(x) = cos(x) and o(h) = [. . .]. Notice o(h) = cos(x)[sin(h) − h] + sin(x)[cos(h) − 1] f (x + h) = f (x) + m · h + o(h) EXAMPLE 5. Differentiate f (x) = sin(x). sin(x + h) = sin(x) + cos(x)h +[− cos(x)h + sin(x + h) − sin(x)] Now, m = f 0(x) = cos(x) and o(h) = [. . .]. Notice o(h) = cos(x)[sin(h) − h] + sin(x)[cos(h) − 1] Therefore, o(h) lim =0 h→0 h Evaluating differentials. Common notations: 0 df (x) = f (x)dx (Compare to df (x)hhi = m · h, substituting m = f 0(x), h = dx) Evaluating differentials. Common notations: 0 df (x) = f (x)dx (Compare to df (x)hhi = m · h, substituting m = f 0(x), h = dx) EXAMPLE 6. d(sin x) = cos xdx, √ 1 d( x) = √ dx, 2 x 1 d(arctan(x)) = dx 1 + x2